Individualistic values, institutional trust, and interventionist attitudes - Hans Pitlik; Martin Rode (Austrian Institute of Economic Research (WIFO), 2016)
Ever since Max Weber (1930) uncovered the cultural origins of capitalism, a common denominator for explanations of economic development is that "individualistic values" provide a more favourable background for promoting the wealth of nations. This paper investigates the impact of individualist values on personal attitudes towards government intervention, as a potential link of culture and formal institutions. We consider two key components of an "individualistic culture" to be particularly relevant for attitude formation, namely values related to self-direction and self-determination. Results indicate that both elements of individualistic values are associated negatively with interventionist preferences. Interestingly, effects of self-direction values on intervention attitudes are much weaker though, than the effects of a strong belief in self-determination. Moreover, the effects of self-direction on intervention preferences are mitigated through higher trust in state actors and lower confidence in major companies, while that does not appear to be the case for self-determination values.
Keywords: D70; D78; H10; L50; 330; individualism; self-direction; self-determination; government intervention; institutional trust; preference formation